Exploring the human emotion of feeling cared for in the workplace. (4th May 2016) - Baggett, Margarita; Giambattista, Laura; Lobbestael, Linda; Pfeiffer, Judith; Madani, Catherina; Modir, Royya; Zamora‐Flyr, Maria Magdalena; Davidson, Judy E.
Abstract : Aim: To explore the emotion of feeling cared for in the workplace. Background: The emotion of feeling cared for drives health‐promoting behaviours. Feeling cared for is the end‐product of caring, affecting practice, environment and outcomes. Identifying behaviours that lead to feeling cared for is the first step in promoting caring practices in leadership. Method: A survey with open‐ended questions was designed, validated and electronically distributed. Data from 35 responses were thematically analysed. Results: Unit culture and leadership style affect caring capacity in the workplace. First level coding revealed two caring behaviour categories: recognition and support. Themes emerged aligned to Chapman's model of workplace appreciation: words of affirmation, receiving gifts, quality time and acts of service. The importance of being treated as a whole person was reported: being appreciated personally and professionally. Feeling cared for drives outcomes such as feeling valued, important, teamwork and organisational loyalty. Conclusions: This study generalises the applicability of Chapman's model developed for workplace appreciation in the health‐care setting. Implications for nursing management: Concrete examples of how leaders stimulate feeling cared for are provided. Caring leadership behaviours have the potential to improve retention, engagement, the healing environment and the capacity for caring for others.